2020
DOI: 10.1515/jhsl-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

History of English as punctuated equilibria? A meta-analysis of the rate of linguistic change in Middle English

Abstract: In this paper, we explore the rate of language change in the history of English. Our main focus is on detecting periods of accelerated change in Middle English (1150–1500), but we also compare the Middle English data with the Early Modern period (1500–1700) in order to establish a longer diachrony for the pace at which English has changed over time. Our study is based on a meta-analysis of existing corpus research, which is made available through a new linguistic resource, the Language Change Database (LCD). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…−− CC BY 4.0 is not limited to the English Civil War but can be seen as part of what Dixon [6] calls "punctuated equilibria", which is the notion that language history is characterized by periods of relative stability punctuated by external events that cause sudden changes in the linguistic situation and hence accelerate the rate of linguistic change. Nevalainen et al [26] have shown that in Middle English, such punctuating events included the Nor man Conquest and the Black Death; at the lexical level, the legacy of the conquest shows up in the many French loanwords in English.…”
Section: Discussionmentioning
confidence: 99%
“…−− CC BY 4.0 is not limited to the English Civil War but can be seen as part of what Dixon [6] calls "punctuated equilibria", which is the notion that language history is characterized by periods of relative stability punctuated by external events that cause sudden changes in the linguistic situation and hence accelerate the rate of linguistic change. Nevalainen et al [26] have shown that in Middle English, such punctuating events included the Nor man Conquest and the Black Death; at the lexical level, the legacy of the conquest shows up in the many French loanwords in English.…”
Section: Discussionmentioning
confidence: 99%
“…We would argue that this phenomenon is not limited to the English Civil War but can be seen as part of what Dixon [6] calls "punctuated equilibria", which is the notion that language history is characterized by periods of relative stability punctuated by external events that cause sudden changes in the linguistic situation and hence accelerate the rate of linguistic change. Nevalainen et al [26] have shown that in Middle English, such punctuating events included the Norman Conquest and the Black Death; at the lexical level, the legacy of the conquest shows up in the many French loanwords in English.…”
Section: Discussionmentioning
confidence: 99%